Analisis Pengaruh Pemasaran Digital Terhadap Loyalitas Pelanggan: System Literatur Review (SLR) - Wibawa, Wira; Yuliana, Yayuk; Hidayat, Toni; Falahi, Adrial (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2025)
This study explores the influence of digital marketing on customer loyalty using a Systematic Literature Review (SLR) method. As digital transformation accelerates, businesses must adapt their marketing strategies to meet changing consumer behaviors. This review analyzes selected journal articles published between 2020 and 2024 to identify trends, key findings, and insights regarding digital marketing's role in fostering customer loyalty. The results indicate that digital marketing tools—such as social media, email campaigns, digital content, and online platforms—positively impact customer loyalty by enhancing customer engagement, personalization, convenience, and brand interaction. Moreover, trust and customer satisfaction emerge as mediating variables in building long-term loyalty in the digital environment. This study provides valuable insights for practitioners to design more effective digital marketing strategies and highlights the importance of aligning digital initiatives with customer expectations. It also contributes to academic research by summarizing recent findings and offering recommendations for future studies.